Analisis Strategi Green Human Resources Management Dalam Menghadapi Tantangan Keberlanjutan Organisasi - Mesatulozisokhi Telaumbanua (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze Green Human Resources Management (GHRM) strategies in addressing organizational sustainability challenges in the modern era characterized by increasing environmental awareness and global pressure for sustainable business practices. The implementation of GHRM is a strategic approach in integrating environmentally friendly principles into the entire human resource management cycle, from green recruitment, environmentally-based training and development, to performance evaluation and sustainability-oriented compensation. The research method used is a qualitative approach with library research techniques and descriptive analysis of various literature, scientific journals, and case studies of companies that have implemented the GHRM concept. The results show that the implementation of GHRM consistently can increase employee environmental awareness, strengthen the company's reputation, and improve operational efficiency through waste reduction and energy consumption. However, the main challenges faced by organizations include limited managerial commitment, employee resistance to change, and the need for policies and organizational culture that support long-term sustainability. This study concludes that the GHRM strategy not only plays a role as an instrument for HR management, but also as a key pillar in creating sustainable competitive advantage.